Killer Fandom Fan Studies and the Celebrity Serial Killer - Fathallah, Judith (Media Manifold Series, 2023)
Killer Fandom is the first long-form treatment of serial killer fandom. Fan studies have mostly ignored this most moralized form of fandom, as a stigmatized Bad Other in implicit tension with the field's successful campaign to recuperate the broader fan category. Yet serial killer fandom, as Judith May Fathallah shows in the book, can be usefully studied with many of the field's leading analytic frameworks. After tracing the pre-digital history of fans, mediated celebrity, and killers, Fathallah examines contemporary fandom through the lens of textual poaching, affective community, subcultural capital, and play. With close readings of fan posts, comments, and mashups on Tumblr, TikTok, and YouTube, alongside documentaries, podcasts, and a thriving "murderabilia" industry, Killer Fandom argues that this fan culture is, in many ways, hard to distinguish from more "mainstream" fandoms. Fan creations around Aileen Wuornos, Jeffrey Dahmer, Ted Bundy, and Richard Ramirez, among others, demonstrate a complex and shifting stance toward their objects-marked by parodic humor and irony in many cases. Killer Fandom ultimately questions-given our crime-and violence-saturated media culture-whether it makes sense to set Dahmer and Wuornos "fans" apart from the rest of us.